SOME OBSERVATIONS ON THE BACKWATER CLAM, MERETRIX CASTA (CHEMNITZ) IN THE BEYPORE AND KORAPUZHA ESTUARIES - Seshappa, G (Indian Journal of Fisheries, 2011)
The backwater clam, Meretrix casta (Chemnitz), is a bivalve mollusc of considerable commercial importance and occurs in estuaries and backwaters of both the east and west coasts of India. Any biological study of this species will therefore be of interest from the scientific and also the fisheries points of view. Before the ’fifties Hornell’s work seems to be the only instance in the country, of any considerable interest in this species (Hornell, 1917 and 1921) both from a systematic and the economic points of view. In 1953 Abraham made some detailed studies on certain aspects of the biology of the species including a study of the environment and also the growth rate under natural as well as experimental conditions, based on material from the Adyar waters near Madras.